Income inequality around the world - Cappellari, Lorenzo; Polachek, S. W.; Tatsiramos, Konstantinos (Emerald, 2016)
Research in Labor Economics 44 takes another in-depth and focussed look at Inequality. This time however it is tied in with well-being of the workforce. Research in Labor Economics volume 44 contains new and innovative research on the causes and consequences of inequality and well-being of the work force.
Keywords: Income distribution.; elektronické knihy; electronic books